PENGARUH PANHISTEREKTOMI TERHADAP RETENSI KALSIUM DAN FOSFOR TIKUS SPRAGUE DAWLEY YANG DIBERI PAKAN KEDELAI SELAMA EMPAT MINGGU - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The objective ofthe current research was to study the effect of panhisterectomy on calcium and phosphor retention in Sprague Dawley rats fed with soybean for four weeks. Ten female Sprague Dawley rats, six weeks of age were randomly divided into two groups (control and panhisterectomized group) of five each. At eight weeks of age, the rats ofpanhisterectomized group were panhisterectomized. At 12 weeks of age, they were placed into individual metabolic cages for balance study. Every morning, from day four to eight of the balance study, the left-over feed was collected for calcium and phosphor analyses. Urine and fecal samples were also collected at the same time. The results of the research showed that calcium and phosphor retentions were significantly reduced (P